ZTA (Zirconium Titanate) ceramic particle preform, preparation and application of ZTA ceramic particle preform in realizing metallurgical interface bonding between ZTA and high-manganese steel matrix

Through the preparation method of the double-layer coated modified ZTA ceramic particles, the problem of poor wettability of ZTA ceramic particles and high manganese steel matrix during casting formation is solved, and the metallurgical bonding and wear resistance are improved, which is suitable for industrial production and engineering applications of composite materials.

CN119800228AActive Publication Date: 2025-04-11JINAN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510015190.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing ZTA ceramic particles and high manganese steel substrates have poor wetting properties during casting and forming, resulting in insufficient mechanical bonding interface and the wear resistance of composite materials is not as expected.

Method used

The preparation method of double-layer coated modified ZTA ceramic particles is adopted to coat ZTA particles by ball milling mixed powder slurry, and sintering is carried out at high temperature to form a double-layer coated layer, improving the wettability of ceramic particles and high manganese steel melt and promoting the formation of metallurgical bonding interface.

Benefits of technology

It significantly improves the interface wettability of ZTA ceramic particles and high manganese steel matrix, realizes metallurgical combination, improves the wear resistance of composite materials, and is suitable for industrial production and large-scale engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229692920000111
    Figure BDA0005229692920000111
  • Figure HDA0005229692930000011
    Figure HDA0005229692930000011
  • Figure HDA0005229692930000012
    Figure HDA0005229692930000012
Patent Text Reader

Abstract

The invention discloses a ZTA ceramic particle prefabricated body, preparation and application of the ZTA ceramic particle prefabricated body in realizing metallurgical interface bonding between ZTA and a high-manganese steel matrix. High manganese steel powder, Zr-Fe powder, ZTA micro powder and ethanol are prepared into slurry by adopting a ball milling process, ZTA particles are soaked in the slurry, taken out, dried and sintered to obtain single-layer coated ZTA particles, then the single-layer coated ZTA particles are soaked in the high manganese steel powder slurry to obtain ZTA particles with two coating layers, the ZTA particles are subjected to pressureless sintering to obtain a ZTA ceramic preform, meanwhile, double-coating-layer curing is achieved, and the ZTA ceramic preform is obtained. And in the casting process, the ZTA ceramic porous preform can effectively promote permeation of a high manganese steel melt and prevent the preform from collapsing under thermal shock. Through the bridge action of the FeZr-ZTA-high manganese steel powder double-layer coating layer, a metallurgical bonding interface is formed between ZTA and a high manganese steel matrix, so that the prepared ZTA ceramic particle reinforced high manganese steel composite material has excellent three-body wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of powder metallurgy and casting, and particularly relates to a double-layer coated modified ZTA ceramic particle porous preform, and a preparation method and application thereof. Background Art

[0002] Wear is common in the fields of metallurgy, petroleum, chemical industry, construction, national defense science and technology, and has a decisive impact on the service reliability and service life of workpieces and equipment. At present, industrial production is increasingly pursuing high-efficiency productivity and sustainable development, but traditional wear-resistant materials can no longer meet performance requirements under severe working conditions. It is urgent to develop new long-lasting wear-resistant materials to fundamentally reduce wear, extend equipment service life, improve production efficiency, and reduce energy loss.

[0003] High manganese steel is a kind of wear-resistant steel designed and developed for heavy industry. When subjected to severe impact or contact stress, the surface of high manganese steel will harden rapidly. Its hard outer and tough inner characteristics can resist both wear and impact. It has been widely used in quarrying, mining, excavation, coal industry, casting and steel industry. Compared with high manganese steel, zirconia toughened alumina (ZTA) ceramic reinforced high manganese steel-based composites can integrate the characteristics of high manganese steel and ZTA ceramics, and are expected to further improve the high-intensity impact resistance, high temperature resistance, wear resistance and other properties of high manganese steel-based materials, which has received extensive attention from academia and engineering circles. However, during the casting process of the composite material, due to the poor wettability of ZTA ceramic particles and high manganese steel melt and the high pouring temperature, the ZTA ceramic particles and the high manganese steel matrix often only form a mechanical bonding interface, and even a physical gap is easily generated between the interfaces of the two, resulting in the composite effect of ZTA ceramics and high manganese steel matrix cannot be exerted, and the overall wear resistance of the composite material is not as expected. In order to achieve low-cost and large-scale production of high-performance ZTA ceramic particle reinforced high manganese steel-based composites, the ZTA ceramic particles must be surface coated to improve the wettability between the ZTA ceramic particles and the high manganese steel matrix through the surface active coating layer and promote the formation of the metallurgical bonding interface, thereby fully exploring the potential composite effect of ZTA ceramic particles and the high manganese steel matrix.

[0004] In order to prevent the ZTA ceramic particles from being impacted by the molten steel during the casting process and collapsing, it is an effective means to prepare the ZTA ceramic particles into a porous preform. To this end, the present invention integrates the double-layer activation coating treatment on the surface of the ZTA ceramic particles with the preparation of the porous preform, develops a preparation method for a double-layer coated modified ZTA ceramic particle porous preform, and applies it to the preparation of ZTA enhanced high manganese steel-based composite materials, which significantly improves the interfacial wettability of the ZTA ceramic particles and the high manganese steel matrix, realizes the metallurgical interface bonding between the two, and greatly improves the wear resistance of the composite material. The interface control strategy involved in the present invention can effectively promote the industrial production and large-scale engineering application of ZTA enhanced high manganese steel-based composite materials, and is also suitable for the development of other iron-based composite materials such as high chromium cast iron and alloy steel, and has very important theoretical and engineering application value. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a double-layer coated modified ZTA ceramic particle porous preform. Specifically, a ball milling process is used to mix high manganese steel powder, Zr-Fe alloy powder, and ZTA micropowder, and anhydrous ethanol is added to make a slurry, and then the ZTA particles are immersed in the slurry to obtain ZTA particles with the slurry coated on the surface, and then sintered at 1050-1100°C, and then the modified ZTA particles are immersed in a slurry composed of high manganese steel powder and anhydrous ethanol to obtain ZTA particles with two layers of coating. On this basis, the two-layer coated ZTA particles are placed in a graphite mold, and a ZTA ceramic porous preform is obtained after pressureless sintering. The preform obtained by this method is conducive to the composite of ZTA ceramics and metal materials, and can also achieve metallurgical bonding between ceramics and metal interfaces.

[0006] Another object of the present invention is to provide a double-layer coated modified ZTA ceramic particle porous preform obtained by the above preparation method.

[0007] Another object of the present invention is to provide an application of the above-mentioned double-layer coated modified ZTA ceramic particle porous preform in a high manganese steel-based composite material.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a double-layer coated modified ZTA ceramic porous preform comprises the following steps:

[0010] (1) Zr-Fe alloy powder, ZTA powder, high manganese steel powder and anhydrous ethanol are mixed by ball milling to obtain a mixed powder slurry;

[0011] (2) immersing the ZTA particles into the mixed powder slurry of step (1) so that the slurry covers the surface of the ZTA particles, taking out the ZTA particles and drying them, and pre-sintering them at 1050-1100° C. to obtain single-layer coated ZTA particles;

[0012] (3) High manganese steel powder and anhydrous ethanol are uniformly mixed to obtain a slurry, and the single-layer coated ZTA particles obtained in step (2) are immersed in the slurry to uniformly coat the surface of the single-layer coated ZTA particles with high manganese steel powder. The particles are taken out and dried, and the ZTA particles with double-layer coating on the surface are loaded into a mold, and pressureless sintering is performed at 1250-1450° C. to obtain a double-layer coated modified porous ZTA ceramic preform.

[0013] Preferably, the particle size of the Zr-Fe alloy powder in step (1) is 200-300 mesh.

[0014] Preferably, in the Zr-Fe alloy powder of step (1), the mass percentage of Zr is 30-60%.

[0015] Preferably, the particle size of the ZTA powder in step (1) is 3 to 5 microns.

[0016] Preferably, the particle size of the high manganese steel powder in steps (1) and (3) is 300-400 mesh.

[0017] Preferably, in step (1), the weight ratio of the Zr-Fe alloy powder, ZTA powder and high manganese steel powder is 4-8:2-6:5-6.

[0018] Preferably, the anhydrous ethanol in step (1) accounts for 15-25% of the weight of the slurry.

[0019] Preferably, the ball milling in step (1) is mechanical ball milling, the ball diameter of the grinding balls is 5 to 10 mm, the weight ratio of the grinding balls to the mixed powder is 5:1 to 8:1, the rotation speed is 250 to 350 r / min, and the ball milling time is 300 to 640 min.

[0020] Preferably, the particle size of the ZTA particles in step (2) is 10 to 15 meshes.

[0021] Preferably, the weight ratio of the ZTA particles to the coating layer mixed powder in step (2) is 5 to 8:1.

[0022] Preferably, the drying in steps (2) and (3) refers to drying under vacuum conditions at 60 to 80° C. for 3 to 4 hours, in order to evaporate and remove the anhydrous ethanol in the particles.

[0023] Preferably, the pre-sintering time in step (2) is 45 to 60 minutes.

[0024] Preferably, in step (3), by weight percentage, high manganese steel powder accounts for 20-27%, anhydrous ethanol accounts for 20-25%, and the remainder is a single layer of coated ZTA particles.

[0025] Preferably, the pressureless sintering time in step (3) is 120 to 180 minutes.

[0026] Preferably, the slurry needs to be stirred during the process of wrapping the particles in steps (2) and (3) in order to mix the raw materials evenly. The rotation speed conventionally used in the art can achieve the purpose of this step, so there is no need to limit the stirring speed.

[0027] The ball milling mixing in step (1), the pre-sintering in step (2), and the pressureless sintering in step (3) are all carried out under an inert gas atmosphere, and the inert gas is at least one of argon, helium and nitrogen.

[0028] The present invention provides a double-layer coated modified ZTA ceramic particle porous preform obtained by the above preparation method.

[0029] The present invention provides application of the above-mentioned double-layer coated modified ZTA ceramic particle porous preform in reinforcing iron-based composite materials.

[0030] The application steps include: fixing the above-mentioned double-layer coated modified ZTA ceramic particle porous preform in a casting cavity, casting an iron-based melt into the cavity, and obtaining a ZTA ceramic particle reinforced iron-based composite material.

[0031] Preferably, the iron base is at least one of high manganese steel, high chromium cast iron and alloy steel.

[0032] The present invention provides a method for preparing a double-layer coated modified ZTA ceramic particle porous preform reinforced high manganese steel composite material, comprising the following steps:

[0033] The above-mentioned double-layer coated modified ZTA ceramic particle porous preform is fixed in a casting cavity, and a high manganese steel melt is cast into the cavity to obtain a composite material with metallurgical bonding at the interface between the ZTA ceramic and the high manganese steel matrix.

[0034] Preferably, the temperature of the high manganese steel melt out of the furnace is controlled at 1520-1570° C., the casting temperature is controlled at 1500±20° C., and slag removal and deoxidation treatment can be performed before casting.

[0035] The above-mentioned method for preparing a double-layer coated modified ZTA ceramic particle porous preform reinforced high manganese steel composite material is a method for achieving metallurgical bonding at the interface between ZTA ceramic particles and a high manganese steel matrix.

[0036] The invention provides a double-layer coated modified ZTA ceramic particle porous preform reinforced high manganese steel composite material prepared by the preparation method.

[0037] The present invention provides application of a double-layer coated modified ZTA ceramic particle porous preform reinforced high manganese steel composite material prepared by the preparation method.

[0038] Preferably, the composite material is used in the fields of metallurgy, mining, construction, machinery and electricity.

[0039] The method of the present invention first coats the surface of ZTA ceramic particles with a coating layer composed of three phases of FeZr-ZTA-high manganese steel powder, and then further coats the high manganese steel coating layer on this basis to prepare a porous preform. The construction of the porous ZTA preform based on the double-layer gradient coating layer can not only effectively improve the wettability between the ZTA ceramic particles and the high manganese steel matrix and construct a metallurgical bonding interface, but also reduce the differences in Young's modulus, thermal expansion coefficient, etc. between ZTA and high manganese steel, thereby improving the interface bonding strength and interface stability.

[0040] The mechanism of the present invention is:

[0041] The present invention obtains a mixed powder by mechanically ball milling and mixing Zr-Fe, ZTA micropowder and high manganese steel powder in a certain ratio, and further coats a high manganese steel powder layer on the surface of ZTA particles after coating the mixed powder, that is, double coating is achieved on the surface of ZTA. Since the coated mixed powder layer contains ZTA micropowder and Zr-Fe alloy powder with good wettability to ZTA, and also contains high manganese steel powder with good wettability to high manganese steel, and the secondary coated high manganese steel powder can further improve the wettability to high manganese steel melt and reduce thermal shock, the introduction of the double coating layer on the surface of ZTA ceramic particles can significantly improve the wettability of ZTA ceramic particles and high manganese steel melt during composite material casting, and can achieve metallurgical interface bonding through component mutual diffusion and limited in-situ interface reaction, so that the prepared ZTA ceramic particle reinforced high manganese steel composite material has excellent three-body wear resistance.

[0042] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0043] (1) The FeZr-ZTA-high manganese steel ternary composite powder and high manganese steel powder double coating layer constructed on the ZTA surface have the dual functions of effectively improving the wettability of ZTA ceramic particles with high manganese steel melt and constructing a composite metallurgical bonding interface, which can efficiently achieve a strong interface bonding between ZTA ceramics and high manganese steel matrix.

[0044] (2) On the basis of achieving double-layer coating on the surface of ZTA ceramic particles, the ZTA ceramic porous preform prepared by low-cost pressureless sintering can effectively promote the infiltration of high manganese steel melt and prevent the preform from collapsing under thermal shock.

[0045] (3) The raw materials used in the present invention can be purchased from the market at a low cost. The prepared ZTA reinforced high manganese steel-based composite material has excellent performance and is conducive to industrial large-scale production and engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Schematic diagram of the construction of metallurgical bonding composite interface of ZTA ceramic particle reinforced high manganese steel composite material.

[0047] Figure 2 This is the morphology of the ZTA porous preform prepared based on double-layer coating on the surface of ZTA ceramics in Example 1.

[0048] Figure 3 This is the ingot diagram of ZTA ceramic particle reinforced high manganese steel matrix composite material. DETAILED DESCRIPTION

[0049] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0050] If the specific conditions are not specified in the examples of the present invention, the conventional conditions or the conditions recommended by the manufacturer are used. The raw materials, reagents, etc. used without specifying the manufacturer are all conventional products that can be purchased commercially. The ball mill used in the examples is a YXQM planetary ball mill.

[0051] Example 1

[0052] (1) Take Zr-Fe powder with a purity of about 99.99% and an average particle size of 200 mesh (the mass percentage of Zr in the Zr-Fe powder is 60%), high manganese steel powder with an average particle size of 300 mesh, and ZTA micropowder with an average particle size of 3 microns, the weight percentage of Zr-Fe alloy powder, ZTA micropowder, and high manganese steel powder is 4:2:5, add anhydrous ethanol mixed powder (accounting for 15% of the total weight of the slurry), and perform mechanical ball milling to obtain a mixed powder slurry. The main ball milling parameters are: grinding ball diameter 5mm, ball-to-material ratio 5:1, rotation speed 250r / min, ball milling time 640min, and nitrogen is used as the protective atmosphere.

[0053] (2) Pour the mixed powder slurry obtained by ball milling in step (1) into a container, and then immerse the ultrasonically cleaned ZTA ceramic particles therein, wherein the average particle size of the ZTA ceramic particles used is 10 mesh, and the weight ratio of the ZTA ceramic particles to the composite powder in step (1) is 5:1, and the ZTA particles are continuously stirred so that they are coated with the slurry, and then taken out and placed in a 60° C. vacuum drying oven for 3 h until the anhydrous ethanol is completely removed, and the coated and dried ZTA particles are sintered at 1050° C. for 45 min in a nitrogen atmosphere, and the furnace is cooled to room temperature and taken out to obtain single-layer coated ZTA particles.

[0054] (3) High manganese steel powder with an average particle size of 300 meshes and anhydrous ethanol are mixed into a uniform slurry, and then the ZTA particles treated with a single layer of coating in (2) are added to the slurry and stirred continuously (by weight percentage, high manganese steel powder accounts for 27%, anhydrous ethanol accounts for 20%, and the balance is the single layer of coated ZTA particles). The ZTA ceramic particles with the slurry on the surface are placed in a corundum mold, and then vacuum dried at 60°C until the anhydrous ethanol is completely removed, and finally pressurelessly sintered at 1250°C for 120 minutes under a nitrogen protective atmosphere to obtain a ZTA porous ceramic preform. The mold size used is 40mm×60mm, and a layer of graphite paper is padded on the inner wall of the mold to facilitate demolding.

[0055] (4) The composite material is prepared by conventional sand casting. The prepared ZTA ceramic preform is fixed in the middle of the casting cavity with a thick iron wire, and a high manganese steel melt is poured into it. The temperature of the high manganese steel melt out of the furnace is controlled at 1550±20°C, and the casting temperature is controlled at 1500±20°C. Before casting, slag removal and deoxidation treatment are performed to obtain a ZTA ceramic particle reinforced high manganese steel-based composite material.

[0056] Schematic diagram of the composite interface structure in the prepared composite material Figure 1 The three-body abrasive wear test was conducted on the ZTA ceramic particle reinforced high manganese steel matrix composite material. The wear test parameters were as follows: the abrasive was 6# quartz sand, the main speed of the wear test machine was 30r / min, the single wear time was 30min (5 times in total, 150min in total), the load was 30N, the radius of the circular rail was 180mm, and each sample was subjected to three wear tests. The wear rate was the average of the three test results. The wear rate of the ZTA ceramic particle reinforced high manganese steel matrix composite material was 0.57mm 3 ·min -1 .

[0057] Example 2

[0058] (1) Take Zr-Fe powder with a purity of about 99.99% and an average particle size of 300 mesh (the mass percentage of Zr in the Zr-Fe powder is 30%), high manganese steel powder with an average particle size of 400 mesh and micro powder with an average particle size of 5 μm, and add anhydrous ethanol (accounting for 20% of the total weight of the slurry) in a weight ratio of Zr-Fe alloy powder: ZTA micro powder: high manganese steel powder = 8:6:6, and mechanically ball mill and mix to obtain a mixed powder slurry. The main ball milling parameters are: grinding ball diameter 10 mm, ball-to-material ratio 8:1, rotation speed 350 r / min, ball milling time 300 min, and nitrogen as the protective atmosphere.

[0059] (2) Pour the mixed powder slurry obtained by ball milling in step (1) into a container, and then immerse the ultrasonically cleaned ZTA ceramic particles therein, wherein the average particle size of the ZTA ceramic particles used is 15 mesh, and the weight ratio of the ZTA ceramic particles to the composite powder in step (1) is 8:1, and the ZTA particles are continuously stirred so that they are coated with the slurry, and then taken out and placed in a vacuum drying oven at 80°C for 4 hours until the anhydrous ethanol is completely removed, and the coated and dried ZTA particles are sintered at 1100°C for 60 minutes in a nitrogen atmosphere, and the furnace is cooled to room temperature and taken out to obtain single-layer coated ZTA particles.

[0060] (3) High manganese steel powder with an average particle size of 400 meshes and anhydrous ethanol are mixed into a uniform slurry, and then the ZTA particles treated with a single layer of coating in (2) are added to the slurry and stirred continuously (by weight percentage, the high manganese steel powder accounts for 20%, the anhydrous ethanol accounts for 25%, and the balance is the single layer of coated ZTA particles). The ZTA ceramic particles with the slurry on the surface are placed in a corundum mold, and then vacuum dried at 80°C until the anhydrous ethanol is completely removed. Finally, the ZTA porous ceramic preform is pressurelessly sintered at 1450°C for 160 minutes under a nitrogen protective atmosphere to obtain a preform. The morphology of the prepared preform is as shown in FIG. Figure 2 The size of the mold used is 40 mm × 60 mm, and a layer of graphite paper is placed on the inner wall of the mold to facilitate demoulding.

[0061] (4) The composite material is prepared by conventional sand casting. The prepared ZTA ceramic preform is fixed in the middle of the casting cavity with a thick iron wire, and high manganese steel melt is poured into it. The temperature of the high manganese steel melt out of the furnace is controlled at 1510±35°C, and the casting temperature is controlled at 1500±20°C. Slag removal and deoxidation treatment are performed before casting to obtain a ZTA ceramic particle reinforced high manganese steel-based composite material.

[0062] The morphology of the ZTA porous preform prepared by double-layer coating on the surface of ZTA ceramics is as follows: Figure 2After three-body abrasive wear test, the wear test parameters are: abrasive is 6# quartz sand, the main speed of the wear tester is 30r / min, the single wear time is 30min (5 times in total, 150min in total), the load is 30N, the radius of the circular rail is 180mm, and each sample is subjected to three wear tests. The wear rate is the average of the three test results. The wear rate of the ZTA ceramic particle reinforced high manganese steel-based composite material is 0.71mm 3 ·min -1 .

[0063] Example 3

[0064] (1) Take Zr-Fe powder with a purity of about 99.99% and an average particle size of 250 mesh (the mass percentage of Zr in the Zr-Fe powder is 40%), high manganese steel powder with an average particle size of 350 mesh, and ZTA powder with an average particle size of 4 μm, and add anhydrous ethanol mixed powder (accounting for 25% of the total weight of the slurry) at a weight ratio of Zr-Fe alloy powder: ZTA powder: high manganese steel powder = 5:4:5, and perform mechanical ball milling to obtain a mixed powder slurry. The main ball milling parameters are: ball diameter of 10 mm, ball-to-material ratio of 6:1, rotation speed of 300 r / min, ball milling time of 480 min, and a nitrogen and argon mixed gas as the protective atmosphere.

[0065] (2) Pour the mixed powder slurry obtained by ball milling in step (1) into a container, and then immerse the ultrasonically cleaned ZTA ceramic particles therein, wherein the average particle size of the ZTA ceramic particles used is 12 mesh, and the weight ratio of the ZTA ceramic particles to the composite powder in step (1) is 6:1, and the ZTA particles are continuously stirred so that they are coated with the slurry, and then taken out and placed in a vacuum drying oven at 80°C for 4 hours until the anhydrous ethanol is completely removed, and the coated and dried ZTA particles are sintered at 1100°C for 50 minutes in a nitrogen atmosphere, and the furnace is cooled to room temperature and taken out to obtain single-layer coated ZTA particles.

[0066] (3) High manganese steel powder with an average particle size of 350 mesh and anhydrous ethanol are mixed into a uniform slurry, and then the ZTA particles treated with a single layer of coating in (2) are added to the slurry and stirred continuously (by weight percentage, high manganese steel powder accounts for 25%, anhydrous ethanol accounts for 21%, and the balance is single-layer coated ZTA particles). The ZTA ceramic particles with the slurry on the surface are placed in a corundum mold, and then vacuum dried at 80°C until all the anhydrous ethanol is removed, and finally pressurelessly sintered at 1400°C for 180 minutes under a nitrogen protective atmosphere to obtain a ZTA porous ceramic preform. The mold size used is 40mm×60mm, and a layer of graphite paper is padded on the inner wall of the mold to facilitate demolding.

[0067] (4) The composite material is prepared by conventional sand casting. The prepared ZTA ceramic preform is fixed in the middle of the mold cavity by a thick iron wire, and the high manganese steel melt is poured into it. The temperature of the high manganese steel melt out of the furnace is controlled at 1530±20°C, and the casting temperature is controlled at 1500±20°C. Before casting, slag removal and deoxidation treatment are performed to obtain a ZTA ceramic particle reinforced high manganese steel-based composite material. The composite material ingot is as follows: Figure 3 shown.

[0068] ZTA ceramic particles reinforced high manganese steel based composite ingots Figure 3 After three-body abrasive wear test, the wear test parameters are: abrasive is 6# quartz sand, the main speed of the wear tester is 30r / min, the single wear time is 30min (5 times in total, 150min in total), the load is 30N, the radius of the circular rail is 180mm, and each sample is subjected to three wear tests. The wear rate is the average of the three test results. The wear rate of the ZTA ceramic particle reinforced high manganese steel-based composite material is 0.64mm 3 ·min -1 .

[0069] Example 4

[0070] (1) Take Zr-Fe powder with a purity of about 99.99% and an average particle size of 250 mesh (the mass percentage of Zr in the Zr-Fe powder is 45%), high manganese steel powder with an average particle size of 300 mesh, and ZTA micropowder with an average particle size of 4 μm, and add anhydrous ethanol mixed powder (accounting for 15% of the total weight of the slurry) at a weight ratio of Zr-Fe alloy powder: ZTA micropowder: high manganese steel powder = 4:2:5, and perform mechanical ball milling to obtain a mixed powder slurry. The main ball milling parameters are: grinding ball diameter 5 mm, ball-to-material ratio 5:1, rotation speed 250 r / min, ball milling time 360 ​​min, and nitrogen as the protective atmosphere.

[0071] (2) Pour the mixed powder slurry obtained by ball milling in step (1) into a container, and then immerse the ultrasonically cleaned ZTA ceramic particles therein, wherein the average particle size of the ZTA ceramic particles used is 10 mesh, and the weight ratio of the ZTA ceramic particles to the composite powder in step (1) is 6:1, and the ZTA particles are continuously stirred so that they are coated with the slurry, and then taken out and placed in a 70°C vacuum drying oven for 3 hours until the anhydrous ethanol is completely removed, and the coated and dried ZTA particles are sintered at 1080°C for 50 minutes in a nitrogen atmosphere, and the furnace is cooled to room temperature and taken out to obtain single-layer coated ZTA particles.

[0072] (3) High manganese steel powder with an average particle size of 350 mesh and anhydrous ethanol are mixed into a uniform slurry, and then the ZTA particles treated with a single layer of coating in (2) are added to the slurry and stirred continuously (by weight percentage, high manganese steel powder accounts for 26%, anhydrous ethanol accounts for 23%, and the balance is single-layer coated ZTA particles). The ZTA ceramic particles with the slurry on the surface are placed in a corundum mold, and then vacuum dried at 70°C until the anhydrous ethanol is completely removed, and finally pressurelessly sintered at 1300°C for 120 minutes under a nitrogen protective atmosphere to obtain a ZTA porous ceramic preform. The mold size used is 40mm×60mm, and a layer of graphite paper is padded on the inner wall of the mold to facilitate demolding.

[0073] (4) The composite material is prepared by conventional sand casting. The prepared ZTA ceramic preform is fixed in the middle of the casting cavity with a thick iron wire, and a high manganese steel melt is poured into it. The temperature of the high manganese steel melt out of the furnace is controlled at 1550±20°C, and the casting temperature is controlled at 1500±20°C. Before casting, slag removal and deoxidation treatment are performed to obtain a ZTA ceramic particle reinforced high manganese steel-based composite material.

[0074] After three-body abrasive wear test, the wear test parameters are: abrasive is 6# quartz sand, the main speed of the wear tester is 30r / min, the single wear time is 30min (5 times in total, a total of 150min), the load is 30N, the radius of the circular rail is 180mm, and each sample is subjected to three wear tests. The wear rate takes the average of the three experimental results. The wear rate of the ZTA ceramic particle reinforced high manganese steel-based composite material is 0.67mm 3 ·min -1 .

[0075] Comparative Example 1

[0076] (1) Take Zr-Fe powder with a purity of about 99.99% and an average particle size of 200 mesh (the mass percentage of Zr in the Zr-Fe powder is 60%), high manganese steel powder with an average particle size of 300 mesh, and ZTA micropowder with an average particle size of 3 μm, and add anhydrous ethanol mixed powder (accounting for 15% of the total weight of the slurry) at a weight ratio of Zr-Fe alloy powder: ZTA micropowder: high manganese steel powder = 4:2:5, and perform mechanical ball milling to obtain a mixed powder slurry. The main ball milling parameters are: grinding ball diameter 5 mm, ball-to-material ratio 5:1, rotation speed 250 r / min, ball milling time 640 min, and nitrogen as the protective atmosphere.

[0077] (2) The mixed powder slurry obtained by ball milling in step (1) is vacuum dried at 60°C for 3 hours until the anhydrous ethanol is completely evaporated, and then directly adhered and wrapped with ZTA ceramic particles (ZTA particle size is 10 mesh) together with a water glass binder (25wt.%), and the weight ratio of ZTA ceramic particles to the composite powder in step (1) is 5:1. Subsequently, the mixed ZTA particles are pressed into a mold, and a ceramic preform is pressed into shape by applying appropriate pressure. The preform and the mold are placed in a drying oven at 60°C for 3 hours, and the mold is taken out after drying to obtain a formed ZTA ceramic preform. The mold size used is 40mm×60mm, and a layer of graphite paper can be placed inside the mold to facilitate demolding.

[0078] (3) The composite material is prepared by conventional sand casting. The prepared ZTA ceramic preform is fixed in the middle of the casting cavity with a thick iron wire. High manganese steel is used as the casting melt. The molten iron temperature is controlled at 1550±20°C and the casting temperature is controlled at 1500±20°C. Slag removal and deoxidation treatment are performed before casting to obtain a ZTA particle reinforced high manganese steel composite material.

[0079] After three-body abrasive wear test, the wear test parameters are: abrasive is 6# quartz sand, the main speed of the wear tester is 30r / min, the single wear time is 30min (5 times in total, 150min in total), the load is 30N, the radius of the circular rail is 180mm, and each sample is subjected to three wear tests. The average value is taken as the final result. The wear rate of the ZTA ceramic particle reinforced high manganese steel-based composite material is 0.83mm 3 ·min -1 .

[0080] Table 1 Three-body wear rate of the composite materials prepared in Examples 1-4 and Comparative Example 1

[0081]

[0082] It can be seen from Table 1 that the wear resistance of the composite materials obtained in Examples 1-4 has certain differences, but they are all significantly better than the wear resistance of the composite material prepared in Comparative Example 1.

[0083] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a double-layer coated modified ZTA ceramic particle porous preform, characterized in that: The following steps are involved: (1) Zr-Fe alloy powder, ZTA powder, high manganese steel powder and anhydrous ethanol are mixed by ball milling to obtain a mixed powder slurry; (2) immersing the ZTA particles into the mixed powder slurry of step (1) so that the slurry covers the surface of the ZTA particles, taking out the ZTA particles and drying them, and pre-sintering them at 1050-1100° C. to obtain single-layer coated ZTA particles; (3) High manganese steel powder and anhydrous ethanol are uniformly mixed to obtain a slurry, and the single-layer coated ZTA particles obtained in step (2) are immersed in the slurry to uniformly coat the surface of the single-layer coated ZTA particles with high manganese steel powder. The particles are taken out and dried, and the ZTA particles with double-layer coating on the surface are loaded into a mold, and pressureless sintering is performed at 1250-1450° C. to obtain a double-layer coated modified porous ZTA ceramic preform.

2. The preparation method according to claim 1, characterized in that: In the Zr-Fe alloy powder of step (1), the mass percentage of Zr is 30-60%; The weight ratio of the Zr-Fe alloy powder, ZTA powder and high manganese steel powder in step (1) is 4-8:2-6:5-6; The anhydrous ethanol in step (1) accounts for 15-25% of the weight of the slurry; The weight ratio of the ZTA particles to the coating layer mixed powder in step (2) is 5 to 8:1; In step (3), by weight percentage, high manganese steel powder accounts for 20-27%, anhydrous ethanol accounts for 20-25%, and the remainder is a single layer of coated ZTA particles.

3. The preparation method according to claim 1 or 2, characterized in that: The particle size of the Zr-Fe alloy powder in step (1) is 200-300 mesh; The particle size of the ZTA powder in step (1) is 3 to 5 microns; The particle size of the high manganese steel powder in steps (1) and (3) is 300-400 mesh; The particle size of the ZTA particles in step (2) is 10 to 15 meshes.

4. The preparation method according to claim 1 or 2, characterized in that: The pre-sintering time in step (2) is 45 to 60 minutes; The time of the pressureless sintering in step (3) is 120 to 180 minutes.

5. The preparation method according to claim 1 or 2, characterized in that: The ball milling in step (1) is a mechanical ball milling, the ball diameter of the grinding balls is 5 to 10 mm, the weight ratio of the grinding balls to the mixed powder is 5:1 to 8:1, the rotation speed is 250 to 350 r / min, and the ball milling time is 300 to 640 min; The ball milling mixing in step (1), the pre-sintering in step (2), and the pressureless sintering in step (3) are all carried out under an inert gas atmosphere, and the inert gas is at least one of argon, helium and nitrogen.

6. A double-layer coated modified ZTA ceramic particle porous preform obtained by the preparation method according to any one of claims 1 to 5.

7. The use of a double-layer coated modified ZTA ceramic particle porous preform as claimed in claim 6 in reinforcing iron-based composite materials, characterized in that: Realize metallurgical bonding at the interface between ZTA ceramics and iron-based substrate.

8. A method for preparing a double-layer coated modified ZTA ceramic particle porous preform reinforced high manganese steel composite material, characterized in that: The following steps are involved: The double-layer coated modified ZTA ceramic particle porous preform according to claim 6 is fixed in a casting cavity, and a high manganese steel melt is cast into the cavity to obtain a composite material with metallurgical bonding at the interface between the ZTA ceramic and the high manganese steel matrix; The high manganese steel melt is controlled at a furnace temperature of 1520-1570°C, and a casting temperature of 1500±20°C.

9. A double-layer coated modified ZTA ceramic particle porous preform reinforced high manganese steel composite material obtained by the preparation method of claim 8.

10. Application of the double-layer coated modified ZTA ceramic particle porous preform reinforced high manganese steel composite material as described in claim 9 in the fields of metallurgy, mining, construction, machinery and electricity.

Citation Information

Patent Citations

  • Multi-channel ceramic perform coated with Ti-Fe micro powder, and preparation method and application thereof

    CN109049267A

  • Manufacturing method for ZTA ceramic reinforced wear-resistant part

    CN112658229A

  • Chemical plating NiMo modified TiB2-TiC particle reinforced high manganese steel-based composite material and preparation method thereof

    CN114833338A

  • Methods for making a metal, sand or ceramic object by additive manufacture and formulations for use in said methods

    GB201808384D0